EFFECT OF MORIN ON LIPIDPEROXIDES AND ANTIOXIDANTS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - S.VISHNUKUMAR; R.STEPHAN (International Journal of Pharma and Bio Sciences, 2012)
The present study investigated the antilipoperoixdative and antioxidant effect of morin in normal and streptozotocin-induced diabetic Wistar rats. Diabetes as induced in rats by an intraperitoneal injection of streptozotocin. Morin was orally administered to normal and diabetic rats for a period of 45 days. In diabetic rats, thiobarbituric acid reactive substances and lipid hydroperoxides were significantly increased, whereas enzymic antioxidants like superoxide dismutase, catalase, glutathione peroxidase and non-enzymic antioxidants (glutathione, vitamin C and vitamin E) were decreased significantly in diabetic rats. Oral administration of morin to diabetic rats significantly decreased the levels of thiobarbituric acid reactive substances and lipid hydroperoxides and increased the levels/activities of enzymatic and non-enzymatic antioxidants. Treatment of normal rats with morin did not significantly alter any of the parameters studied. Thus, morin exhibits free radical scavenging and antioxidant properties in streptozotocin-induced diabetic rats.